Stepping out of the shadows of Alzheimer's disease: a phenomenological hermeneutic study of older people with Alzheimer's disease caring for a therapy dog. Issue 1 (1st January 2017) - Swall, Anna; Ebbeskog, Britt; Lundh Hagelin, Carina; Fagerberg, Ingegerd
ABSTRACT: Purpose : Living with Alzheimer's disease (AD) can involve a person being unable to recall and convey information in daily life. There are several ways to provide person-centred care to older people with AD, e.g. by empowering them in a situation. The use of animal-assisted therapy (AAT) with a therapy dog in the care of people with dementia is increasing, with the presence of a therapy dog being described as improving, among other things, the well-being and socialization of the person. The aim of this study was to illuminate meanings of care for people with AD in their encounters with a therapy dog. Method : The study used video-recorded observations of the person with AD and the dog. Data were transcribed and analysed using a phenomenological hermeneutic method. Results : The main theme was "Using one's own resources and abilities as a human being", which meant being the person one can be and distancing oneself from the symptoms of AD during the time with the dog. Conclusions : The feelings evoked in the people with AD included empathy and altruism, which allowed for a sense of joy and tenderness, which may induce a sense of self-worth, of being needed, and of being meaningful.